PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Susy Muchtar; Elsa Darari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2013)
The purpose of this research is to determine the effect of corporate governance on the firm performance of companies listed in the Indonesia Stock Exchange.The sample examined in this research consist of 40 manufacturing companies in Indonesia Stock Exchange (BEI) from 2008 to 2012 using purpose sampling as its sample selection techniques. Independent variables from this research are board structure, board committees, board meetings, board size, executive directors and independent non-executive directors. Dependent variables are return on assets (ROA) and return on equity (ROE). The analysis method use are the classical assumption test, multiple regression, and the t test. the result of the t test showed, board structure has no effect on corporate performance as measured by return on assets (ROA), but a negative effect on company performance as measured by return on equity (ROE),board committees positive effect on the firm performance, board meetings had no influence on the performance of the company, board size has a positive effect on the firm performance, executive directors do not have an influence on the company’s performance as measured by return on assets (ROA) and return on equity (ROE), independent non-executive directors have a negative effect on corporate performance as measured by return on assets (ROA), but does not affect the company’s performance as measured by return on equity (ROE).Keywords: Corporate governance, firm performance, board structure, board committee, board meeting, board size, executive directors, independent non executive directors, return on asset, return on equity.